Schooling and decentralization patterns and policy implications in Francophone West Africa - Lugaz, Candy (Management reform for EFA, 2010)
"Decentralization has been a fashionable management reform for quite a few years, in countries with very different characteristics. Little is known however about its implementation at local level or its impact on the functioning of schools and district education offices. This study is based on extensive field research in four West-African countries (Benin, Guinea, Mali and Senegal), undertaken in collaboration with ministries of education, national research institutes and the NGO, Plan. It demonstrates the challenges that the implementation of decentralization encounters at local level. The lack of transparency, the unequal distribution of power, the weakness of the state and its local representatives as well as the scarcity of resources help explain why decentralization does not necessarily lead to improvement. However, many innovative initiatives are being undertaken. They help to identify principles of good practice, such as the need for complementarity between actors and for ensuring equilibrium between their mandate and resources. Autonomy has to be counterbalanced by professionalism and an effective accountability framework. One principle stands central: decentralization does not imply that the state is abandoning control, but it demands a change in its role, towards more support and a stronger focus on equity."--www.iiep.unesco.org.